2008
DOI: 10.1158/0008-5472.can-07-5348
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor β Induces Apoptosis through Repressing the Phosphoinositide 3-Kinase/AKT/Survivin Pathway in Colon Cancer Cells

Abstract: FET cells, derived from an early-stage colon carcinoma, are nontumorigenic in athymic mice. Stable transfection of a dominant-negative transforming growth factor B (TGFB) type II receptor (DNRII) into FET cells that express autocrine TGFB shows loss of TGFB signaling and increased tumorigenicity in vivo indicating tumor suppressor activity of TGFB signaling in this model. The ability of tumorigenic cells to withstand growth factor and nutrient deprivation stress (GFDS) is widely regarded as a key attribute for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 41 publications
(63 reference statements)
4
115
0
Order By: Relevance
“…These results indicate that PDK4 regulates the expression of Bcl-2 and survivin. It has been shown that Bcl-2 and survivin protect colon cancer cells from stress-induced apoptosis (35,36) and that 5-FU induces apoptosis in colon cancer cell lines with modulation of Bcl-2 family proteins (37). To demonstrate the potential role of Bcl-2 and survivin in 5-FU-induced apoptosis in PDK4 knockdown cells, Bcl-2 and survivin were ectopically expressed individually in CBS/PDK4 sh-2 cells.…”
Section: Genetic or Pharmacological Inhibition Of Pdk4 Sensitizes Colmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicate that PDK4 regulates the expression of Bcl-2 and survivin. It has been shown that Bcl-2 and survivin protect colon cancer cells from stress-induced apoptosis (35,36) and that 5-FU induces apoptosis in colon cancer cell lines with modulation of Bcl-2 family proteins (37). To demonstrate the potential role of Bcl-2 and survivin in 5-FU-induced apoptosis in PDK4 knockdown cells, Bcl-2 and survivin were ectopically expressed individually in CBS/PDK4 sh-2 cells.…”
Section: Genetic or Pharmacological Inhibition Of Pdk4 Sensitizes Colmentioning
confidence: 99%
“…One important difference between 5-FU-sensitive and -resistant cells is TGF␤ signaling. Although 5-FU-sensitive RKO and HCT116 cells are defective in TGF␤ signaling because of the mutations in TGF␤ RII (3), 5-FU resistant FET and CBS cells are responsive or partially responsive to TGF␤ signaling, respectively (36,38). This suggests that the TGF␤ signaling pathway may play a role in the 5-FU response.…”
Section: Tgf␤ Signaling Mediates Drugmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, a body of evidence suggests that constitutive activation of mTORC1 in AML is independent of PI3K which in turn can be constitutively fully activated in an mTOR-independent manner. 29 Previous studies have demonstrated that PI3K/Akt inhibitors caused decreased expression of many proteins including survivin 17,18,[30][31][32] in solid tumors and hematologic malignancies. Additionally, it has been shown in a mouse model that internal tandem duplication of Flt3 regulates survivin expression via PI3K/Akt leading to aberrant progenitor cell proliferation and promoting leukemogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…15 Additionally, it has been shown in a mouse model that internal tandem duplication of Flt-3 regulates survivin expression via PI3K/Akt leading to aberrant progenitor cell proliferation. 16 Although the importance of the PI3K/Akt/survivin pathway has been reported in lung and colon cancer, 17,18 its incidence and prognostic impact in AML have not been described.In this study we analyzed the subcellular compartment distribution of WT survivin and the splicing variants survivin-2B and survivin-Delta-Ex3 in AML patients, the correlation with PI3K/Akt pathway activation, and the possible impact on outcome. …”
mentioning
confidence: 99%